2022
DOI: 10.3390/ijms23042056
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Antioxidants from Natural Products on Obesity, Dyslipidemia, Diabetes and Their Molecular Signaling Mechanism

Abstract: Obesity is a risk factor that leads to the development of other diseases such as dyslipidemia and diabetes. These three metabolic disorders can occur simultaneously, hence, the treatment requires many drugs. Antioxidant compounds have been reported to have activities against obesity, dyslipidemia and diabetes via several mechanisms. This review aims to discuss the antioxidant compounds that have activity against obesity, dyslipidemia and diabetes together with their molecular signaling mechanism. The literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 131 publications
(150 reference statements)
0
25
0
Order By: Relevance
“…To date, there is no approved treatment available for NAFLD. Medicinal herbs with high phenolic content have been explored as a safe and convenient treatment option for NAFLD, as they are known to have beneficial anti-inflammatory and antifibrogenic activity, and antioxidant effects, and can suppress hepatic lipid accumulation [ 17 ]. The current study showed strong evidence of the anti-steatotic effect of O. aristatus by using HFD-fed mice and a palmitic–oleic acid-induced model of NAFLD in HepG2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is no approved treatment available for NAFLD. Medicinal herbs with high phenolic content have been explored as a safe and convenient treatment option for NAFLD, as they are known to have beneficial anti-inflammatory and antifibrogenic activity, and antioxidant effects, and can suppress hepatic lipid accumulation [ 17 ]. The current study showed strong evidence of the anti-steatotic effect of O. aristatus by using HFD-fed mice and a palmitic–oleic acid-induced model of NAFLD in HepG2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidants have a crucial role in the prevention and treatment of atherosclerosis through different mechanisms: the inhibition of LDL oxidation, the reduction of reactive oxygen species (ROS) generation, the prevention of atherosclerotic plaque formation and platelet aggregation, improvement of endothelial dysfunction, and vasodilation, the augmentation of NO bioavailability, and suppression of foam cell formation. 26,27 NO has a number of intracellular effects that lead to vasorelaxation, endothelial regeneration, inhibition of lipid peroxidation, inhibition of leukocyte chemotaxis, and platelet adhesion, which are important mechanisms in the prevention of atherosclerosis. 28,29 Besides, CoQ10, curcumin, resveratrol, quercetin, and berberine have an effect on regulating dyslipidemia via different mechanisms and contribute to the anti-atherosclerotic effect of Nano NO plus.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it represents enormous socio-economic and negative impacts on patient's social and psychological attitude. [2][3][4][5][6] Currently, several therapeutic plans are implemented for the treatment and/or prevention of obesity including lifestyle, nutrition education, and anti-obesity medications. 7,8 However, it is reported that weight management through physical exercises are not sufficient to produce marked treatment.…”
Section: Introductionmentioning
confidence: 99%